Sensors and Wearable Technologies in Sport Technologies, Trends and Approaches for Implementation - James, Daniel A.; Petrone, Nicola; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2016)
This book explores emerging trends in wearable sensors for sport and highlights the developments taking place. Drawing on the literature both the approaches and principals for the use of sensors in sport are outlined, and together with references to key works the reader finds this useful in considering such endeavours. The development of wearable technologies is fast paced and accompanying that is an exponential growth in the use and development of computing resources, thus while the review is comprehensive on content not all works can be included and given publication times will inevitably be somewhat dated. The illumination through trends, examples and principles are an aid for anyone considering the use of sensors and wearables in sports.
Introduction -- Review -- Sensors -- Approaches -- Implementation -- Future Directions -- Conclusions.
Keywords: Biomedical engineering; Sports sciences; Signal processing; Biomedical Engineering and Bioengineering; Sport Science; Signal, Speech and Image Processing